Whistleblowing – Need for harmonization on the European Union level? - Eisanen, Kaisa (fi=Turun yliopisto|en=University of Turku|, 2016)
The subject of this study is the whistleblower protection in the European Union. The object of this study is to determine the current level of whistleblower protection in the European Union by comparing the level of protection provided on the European Union level and by the case law of the European Court of Human Rights to the level of protection provided by the national legislations of the United Kingdom and Finland. The study is theoretical and is based on legal literature, legislation, international treaties, case law and the recent studies ordered by the European Commission. The aim of this study is also to critically assess the need for European Union level protection for whistleblowers, the possible functioning of such legislation and the competence of the European Union to legislate whistleblower protection through a harmonized legislative act. Currently the European Union does not regulate the protection of whistleblowers. Only some European Union Member States have implemented exclusive national whistleblowing or whistleblower protection laws. The other European Union Member States have regulated whistleblowing and whistleblower protection through labour law, commercial law, financial law, environmental law and criminal law but the protection provided for whistleblowers in these Member States is either limited or non-existent. There is neither unified terminology within the Member States for the material and personal scope of whistleblowing, reporting procedures, or the level of protection provided to whistleblowers. Whistleblowing has been recognized as one of the most effective tools in preventing and exposing fraud, corruption and other illegal activities in the internal market. Leaving the national legislators with a significant amount of flexibility in implementing whistleblower protection laws may result in substantially different levels of protection throughout the European Union. A comprehensive definition of the material scope of whistleblowing and extensive whistleblower protection in the European Union would be of paramount importance in ensuring that European employees can report or disclose information of public interest.